Flora y vegetación briofítica de la Sierra del Relumbrar (SO de Albacete, España) - Heras-ibáñez, Jorge de las; Ros, Rosa María; Guerra, Juan (Lazaroa, 1989)
Heras-Ibáñez. J. de las, J., Ros. R. M.~ & Guerra, J. Bryophyiic flora and vegetation of ¡he Sierra del Relumbrar (SW of A/bace¡e, Spainj Lazaroa 11: 149-175 (1989). A brophytic and phytosociologic study of the Sierra del Relumbrar (SW of Albacete, Spain) is made. The caíalogue presenís 136 taxa (23 liverworts and 133 mosses). It includes 34 new [br Albacete province and 19 [br he SE ol? Spain. Bryophytic conirnunities are analysed. Sorne of ihem can be assignated to previously known associations in the Iberian Peninsula and a new one is described.